The Inter-American Court of Human Rights Decisions and Non-Repetition Measures on the Right to Health in Latin America - Ana Carolina Girard Teixeira Cazetta; Alberto do Amaral Júnior (Revista Direito GV)
Abstract This paper aims to analyze the evolution of case law regarding the understanding of the right to health in the Inter-American Court of Human Rights. This work hypothesizes that the time it took to understand the right to health as autonomous has directly impacted its interpretation and the formulation of reparatory measures. The autonomy of the right to health is important because it allows this right to be analyzed at its core; in other words, it is not merely an aspect of any other right, but has its own specificities. The article was written after examining all cases related to the right to health and its non-repetition measures. It presents a new way of studying those decisions, by categorizing them into three periods of the Court’s understanding, after observing that there was a pattern within a specific period. This article will help all actors in the international protection of human rights to understand standards and the state’s obligation regarding the right to health in Latin America.